Controlled-flow Instruments for Simulating in Vivo Thrombosis - Clark, H. G; Shinoda, B. A; Mason, R. G (Thrombosis and Haemostasis, 1973)
A technique has been developed which allows an estimation of the clotting tendency of blood under conditions which simulate in vivo flow in various regions of the circulatory system. Minimum contact between blood and foreign surfaces other than the walls of the tubular test cell is obtained. Early pre-clotting and clotting events which alter the apparent viscosity of blood are resolved within three seconds of their onset. Increases in apparent viscosity slow the oscillations of the test system, and frequency, differential frequency, or amplitude can be monitored continuously. A standard tubing material may be used to evaluate effects of antithrombotic or other agents. For the present studies, the instrument was used with native blood at 28° or 37° C to produce shear rates comparable to those present in venous flow. Gum rubber, vinyl, glass and silicone tubing have been investigated for their effects on activation of the intrinsic coagulation system of human blood. In order of increasing-time to formation of thrombus are glass, vinyl, rubber, silicone. Thrombi were adherent to glass and rubber but not to Tygon or Silastic tubes. Time sequence studies during flow in silicone tube with native blood indicate progressive shortening of Stypven and partial thromboplastin time values, and progressive decrease in leukocyte and platelet counts. Addition of a commercial bovine collagen preparation to native normal blood in Silicone tubing decreased the thrombus time value by 40% while addition of the experimental agents RA 233 or VK 744 decreased this value by 50% and 70% respectively. Aspirin therapy produced a 158% increase in thrombus time values. Light microscopic studies of thrombi formed in this closed system revealed thrombus structure comparable to that of classic venous thrombi.